Polyploidy can Confer Superiority to West African Acacia senegal (L.) Willd. Trees - Diallo, Adja M.; Nielsen, Lene R.; Kjær, Erik D.; Petersen, Karen K.; Ræbild, Anders (Frontiers in Plant Science, 2016)
Polyploidy is a common phenomenon in the evolution of angiosperms. It has been suggested that polyploids manage harsh environments better than their diploid relatives but empirical data supporting this hypothesis are scarce, especially for trees. Using microsatellite markers and flow cytometry, we examine the frequency of polyploids and diploids in a progeny trial testing four different populations of Acacia senegal, a species native to sub-Saharan regions of Africa. We compare growth between cytotypes and test whether polyploid seedlings grow better than diploids. Our results show that polyploids coexist with diploids in highly variable proportions among populations in Senegal. Acacia senegal genotypes were predominantly diploid and tetraploid, but triploid, pentaploid, hexaploid and octaploid forms were also found. We find that polyploids show faster growth than diploids under our test conditions: in an 18 years old field trial, polyploid superiority was estimated to be 17% in trunk diameter and 9% in height while in a growth chamber experiment, polyploids grew 28 % taller, but only after being exposed to drought stress. The results suggest that polyploid A. senegal can have an adaptive advantage in some regions of Africa.